Personalised long-term follow-up of cochlear implant patients using remote care, compared with those on the standard care pathway: study protocol for a feasibility randomised controlled trial - Cullington, Helen; Kitterick, Pádraig T.; DeBold, Lisa; Weal, Mark; Clarke, Nicholas; Newberry, Eva; Aubert, Lisa (BMJ Publishing Group, 2016)
Introduction: Many resources are required to provide postoperative care to patients who receive a cochlear implant. The implant service commits to lifetime follow-up. The patient commits to regular adjustment and rehabilitation appointments in the first year and annual follow-up appointments thereafter. Offering remote follow-up may result in more stable hearing, reduced patient travel expense, time and disruption, more empowered patients, greater equality in service delivery and more freedom to optimise the allocation of clinic resources.